2010
DOI: 10.1177/1934578x1000500323
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Leaf Essential Oil Composition of Zanthoxylum clava-herculis growing in Huntsville, Alabama

Abstract: The seasonal variation in the chemical composition of the leaf essential oil of Zanthoxylum clava-herculis has been analyzed by GC-MS. Three individual trees were sampled four times during the course of the 2004 growing season. Notable differences were recorded in the essential oil yields from the three trees on the four collection dates; yields were highest in May and lowest in July The leaf essential oils were made up of 25 components, largely menthane monoterpenoids, dominated by limonene (44-73%) and 1,8-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Trunk bark essential oils have a lower chemical variability, probably due to the fact that the trunk bark formation is slow, and thus less impacted by environmental factors [53]. Results are supported by the fact that seasonal differences in the chemical composition of essential oils from fruits, trunk bark and leaves have already been highlighted for other Zanthoxylum species [21,23]. Indeed, while the chemical compositions of essential oils are genetically determined, it can be considerably modified by factors such as temperature, light, seasonality, water availability and nutrition.…”
Section: Seasonal Effect On Essential Oil Compositionmentioning
confidence: 69%
“…Trunk bark essential oils have a lower chemical variability, probably due to the fact that the trunk bark formation is slow, and thus less impacted by environmental factors [53]. Results are supported by the fact that seasonal differences in the chemical composition of essential oils from fruits, trunk bark and leaves have already been highlighted for other Zanthoxylum species [21,23]. Indeed, while the chemical compositions of essential oils are genetically determined, it can be considerably modified by factors such as temperature, light, seasonality, water availability and nutrition.…”
Section: Seasonal Effect On Essential Oil Compositionmentioning
confidence: 69%
“…Liu et al [ 18 ] showed that the essential oil of Zanthoxylum avicennae leaves and stems had high content of monoterpenoids including 53.05% eucalyptol. Prieto et al [ 19 ] determined the major constituents of Zanthoxylum monophyllum oil were eucalyptol (9.19%); Eiter et al [ 20 ] analysed the essential oil from Zanthoxylum clava - herculis and found the content of eucalyptol ranged from 16 to 43%. Similar research was also carried out on the essential oil from the fruits of Zanthoxylum bungeanum [ 21 ]; Zanthoxylum rhetsoides and Zanthoxylum myriacanthum [ 22 ], the content of eucalyptol is 16.0% 15.7% and 18%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The most abundant compounds in the bark essential oil of Z. clava-herculis were sabinene (47.0%), limonene (18.7%), and terpinen-4-ol (12.9%). In comparison, the leaf essential oils of Z. clava-herculis are dominated by limonene (43.6-73.0%) and 1,8cineole (12.9-43.3%), with only trace amounts of sabinene or terpinen-4-ol [3]. The bark essential oil of Z. tetraspermum showed neither sabinene nor limonene nor any monoterpenoids, but was dominated by caryophyllene oxide (71%) [5].…”
mentioning
confidence: 91%
“…Zanthoxylum clava-herculis L., commonly known as toothache tree, Southern prickly-ash, or Hercules's club, is a small deciduous tree, native to southeastern United States. The bark of Z. clava-herculis has been used by native Americans for chronic rheumatism, dyspepsia, dysentery, kidney trouble, heart trouble, colds, coughs, lung ailments, toothache, and nervous debility (see [3] and references cited therein).…”
mentioning
confidence: 99%